Land Reforms and Social Change Study of a Kerala Village - P\Radhakrishnan (ECONOMIC AND POLITICAL WEEKLY 1983, 1983)
The implementation of the Kerala Land Reforms (Amendment) Act of 1969 has led to loss of land by the group in which land was traditionally concentrated, namely the Nambootiris. Consequently, the Nambootiris have also lost the status, power and authority which they Enjoyed in the villages during the pre-reform period. The gain of land by the groups which were traditionally dependent on the Nambootiris as cultivatingtenants, viz, the Ambalavasis, Nayars, Maniyanis, Vaniyas ami the Tiyyas, has brought about a marked improvement in their economic condition, and altered the traditional patron-client and reciprocal and redistributive relationships which characterised the pre-reform village economy and society. It has also transformed the pre-reform subservient socio-economic relations of these groups, towards the Nambootiris, into egalitarian relations. The remaining four groups, viz, the Mavaris, artisans and service castes, harijans and the Mappilas, have not benefited much by the redistribution of land, especially wet land.